DECODING CONSUMER CHOICES: NAVIGATING THE IMPACT OF ZERO MOMENT OF TRUTH ON BUYING DECISIONS IN BENGKALIS ISLAND - Putra, Halim Dwi (JURNAL ILMIAH EDUNOMIKA, 2024)
In the era of the Internet, where consumers are perpetually connected and information about diverse products is readily accessible, the dynamics of the consumer purchase decision process have undergone a profound transformation. This shift is marked by an increased emphasis on information-seeking activities before the physical encounter with products on store shelves. Two pivotal concepts, the First Moment of Truth (FMoT) and the Zero Moment of Truth (ZMoT), have emerged to elucidate crucial junctures in this process. FMoT underscores the significance of the in-store experience and the initial seconds when consumers engage with brands on shelves. In contrast, ZMoT spotlights the online research phase preceding the purchase decision, encompassing the use of electronic Word of Mouth (e-WoM) to make informed choices. This paper delves into the theoretical underpinnings of the ZMoT concept, establishing connections with existing academic literature. Additionally, it draws on a prior study conducted in the US market as a reference point to explore the impact of the Zero Moment of Truth on consumer behavior in the context of Bengkalis Island. The research scrutinizes results across diverse demographic segments, offering valuable insights into the nuanced interplay between ZMoT and actual buying behavior. Ultimately, these findings are juxtaposed with those of previous research, enriching our understanding of the evolving landscape of consumer decision-making. Keywords: Zero Moment of Truth (ZMoT), buying decision process and impulse buying